On the use of lignocellulosic hemp fibers to produce biodegradable cost-efficient biocomposites - Jéssica Fernanda Pereira; Eugenia Núñez; Alcira Reyes; Suzana Mali; Amparo Lopez-Rubio; María José Fabra (Future Foods)
In this study, the ability of natural hemp fibers (HF) to act as fillers in biodegradable biocomposites has been evaluated by mixing different concentrations of HF with commercially- available biodegradable polyesters, aiming at incorporating the maximum amount of HF to obtain a cost-effective new material in a sustainable approach. Blends of poly(hydroxy‑butyrate) (PHBV) and poly (butylene adipate-co-terephthalate) (PBAT) were used as polymeric matrix. HF were washed and ground before use. They were mainly composed of lignin (̴ 22 %) and carbohydrates (̴ 62–67 %) but a significant amount of proteins (̴ 8.77 %) was also detected. The polymer-HF composites were produced by melt-compounding using mild conditions and shaped as films by compression-molding to obtain test specimens used in the characterization of the biocomposites. The effect of HF loading on the final performance of the biocomposites was investigated. Interestingly, up of 40 % of HF could be incorporated as fillers into the PHBV-PBAT polymeric matrix. The incorporation of HF improved mechanical performance when compared to the polyester blends. In order to reduce its water sensitivity of the composites, food-grade beeswax or carnauba wax were incorporated within the polymeric matrix filled with HF, and the resulting biocomposites showed similar mechanical properties than their counterparts prepared without waxes but displayed significantly higher hydrophobicity.